Penerapan Metode Demonstrasi dalam Meningkatkan Kemampuan Praktek Salat Siswa Kelas IV di SD Al-Azhar 1 Kota Batam - Afi Parnawi; Bayu Mujrimin; Yuli Fatimah Waro Sari; Bagus Wahyudi Ramadhan (Departement of Mathematics Education, 2023)
School is a place where a student takes education and obtains learning both material learning and learning that will be useful in society. In the teaching and learning process, a teacher has an important role where the teacher is tasked with transferring the knowledge needed by his students. Teachers are also required to be able to choose the right methods and strategies in the learning process in order to create good and appropriate learning. The selection of strategies and methods greatly influences the success of teachers in transferring knowledge. The practice of prayer is one of the subjects of Islamic Religious Education subjects. In the process of practicing this prayer there are still various difficulties experienced by students, starting from mistakes in prayer movements to reading prayers. So that the prayer process is still not quite right. This is of course a problem so that with the application of the demonstration method it is hoped that there will be changes and good results from the movements and reading of students' prayers.